Participação da comunidade na autoavaliação institucional em universidades da Argentina, Brasil e Paraguai - Amâncio, Weslei Trevizan (2019)
This paper analyzes the participation of the community in the institutional self - assessment carried out in certain public universities of Argentina (UNNE), Brazil (UFFS, UTFPR) and Paraguay (UNE). The theoretical basis was based on a review of the specialized bibliography of the theme; the methodological resources used are the comparative study, the documentary research and the content analysis, with quantitative and qualitative approaches. We assume that the procedures and instruments adopted in the self-assessment processes carried out in universities, as well as the way of operationalization, are influenced by neoliberal policies, and given the models of managerialist management and the conception of objectivist evaluation in their environment, there is centralization and concentration of strategic decisions and the participation of the community occurs in an instrumental way, hampering their involvement in the processes and potential achievements and transformative that can mean the evaluation action. The analysis of the data shows that the definitions about self-assessment are restricted to organs and commissions with defined cuts and the composition of a small fraction of the institutional actors who are in charge of carrying out all the operationalization of the self-assessment processes. Thus, the centralization and concentration of the strategic decision spaces of the institution is a present reality and with significant relevance in the researched universities. With regard to the self-assessment process, many institutional actors have been absent, especially in the elaboration of contents and instruments. The participation, otherwise, when it occurs, has been constituted by a low adhesion and little representative of the university community, being too instrumentalised, partial and based on the quest to establish quantitative and summative results. Against this background, we point out that there is much to be re-evaluated, reflected and specially corrected and developed in the self-rated processes studied, particularly with regard to community participation and involvement in its elaboration, planning, execution, that is, in the construction of the action evaluation as a whole. We conclude that it is necessary to problematize the meanings of the institutional self-assessment processes that are circumscribed to the researched universities, by promoting the debate about the elaboration, structuring and intensification of participatory processes, through which the guide is, in a perspective of formative and emancipatory evaluation, knowledge of the institution and commitment to transformation, with a view to academic-scientific improvement and strengthening of the university's ethical, democratic and social responsibility and commitment.